Development and Validation of a Rapid and Efficient Prognostic Scoring System for Sepsis Based on Oxygenation Index, Lactate and Glasgow Coma Scale - Lai Q; Xia Y; Yang W; Zhou Y (Dove Medical Press, 2023)
Qiang Lai,1- 3 Yiqin Xia,1- 3 Wentao Yang,1- 3 Yiwu Zhou1- 3 1Emergency Department, West China Hospital, Sichuan University, Chengdu, Sichuan, People's Republic of China; 2Laboratory of Emergency Medicine, West China Hospital, Sichuan University, Chengdu, Sichuan, People's Republic of China; 3Disaster Medical Center, Sichuan University, Chengdu, Sichuan, People's Republic of ChinaCorrespondence: Yiwu Zhou, Emergency Department, West China Hospital of Sichuan University, Chengdu, Sichuan, People's Republic of China, Email 456zyw@163.comObjective: To develop a concise scoring system for efficient and rapid assessment of sepsis prognosis applicable to emergency departments.Methods: This was a single-center retrospective cohort study of patients with sepsis. In this study, a new scoring system (oxygenation index, lactate, and Glasgow coma scale: GOL) was developed through a derivation group, and then the GOL was validated using a validation group. Multivariate logistic regression analysis was performed to investigate the relationship between GOL and 28-day adverse outcomes. The GOL was compared with the previous scoring system using receiver operating characteristic curves (ROC) and decision analysis curves. The endpoints of this study were mortality, mechanical ventilation (MV), and admission to the intensive care unit (AICU).Results: 608 patients were included in the derivation group and 213 patients in the validation group, with 131 and 42 deaths, respectively. In the validation group, lactate (Lac), oxygenation index (PaO2/FiO2), and Glasgow coma scale score (GCS), the three best performers in predicting 28-day mortality from receiver operating characteristic curves, were used to construct the GOL. The higher the GOL score, the higher the incidence of death, MV and AICU within 28 days. Multifactorial logistic regression analysis showed that when the GOL was greater than 1, it was an independent risk factor for 28-day mortality, MV, and AICU. In predicting 28-day mortality, GOL was superior to the quick Sequential Organ Failure Assessment (qSOFA), Mortality in Emergency Department Sepsis Score (MEDS), Systemic Inflammatory Response Syndrome Score (SIRS), and Modified Early Warning Score (MEWS), and was comparable to the Acute Physiology and Chronic Health Evaluation (APACHE) II and Sequential Organ Failure Assessment (SOFA).Conclusion: The GOL is a simple, rapid, and accurate method for early identification of patients at increased risk of in-hospital death from sepsis.Keywords: sepsis, GCS, lactic acid, oxygenation index, PaO2/FiO2, prognosis